MENGUKUR INDEKS KEPUASAN MASYARAKAT (IKM) TERHADAP PELAYANAN PUBLIK PADA ORGANISASI SEKTOR PUBLIK KELURAHAN - Ahmad Sururi (Yogyakarta State University, 2019)
The purpose of this study was to find out how much the level of community satisfaction with public services in urban public sector organizations, namely Cipare Serang Urban Village. The research method used is a quantitative approach. The population in this study amounted to 80 people with an error rate of 1% and obtained results of 44 people as a sample. Data collection techniques use observation (observation), interviews (interviews) and questionnaires (questionnaires). The research instrument as stated in the Minister of Administrative Reform and Bureaucratic Reform Regulation Number 14 of 2017 concerning Guidelines for Preparing the Community Satisfaction Survey. The results of the study, it can be concluded that the Community Satisfaction Index in Cipare Village has gone well. This can be seen from 9 (nine) appropriate indicators (Permenpan-RB) Number 14 of 2017 with the average service quality in the Good category with the IKM conversion value of = 77,650. However, there are still shortcomings in the completion time indicator and indicators for handling complaints, suggestions and inputs in the unfavorable category.